(untitled) (Legal journal - Research in Legal and Social Sciences, 2021)
In 2013, the Public Ministry of Paraguay signed an agreement with the non-governmental entity with the National Center for Missing and Exploited Children of the United States, from now on NCMEC. The agreement consists of the cooperation between both institutions, by NCMEC giving access to a VPN to its Cybertipline system that has reports of cases of pornography related to children and adolescents reported by the electronic service provider in which the alleged perpetrator has used an IP address whose geolocation corresponds to an internet provider company that establishes residence in our country and the investigation of each case by the Paraguayan prosecutor’s office. The general objective of this research work is to establish the obstacles that exist in the investigation of cases of child pornography reported through the Cybertipline system. The specific objectives are; determine the average number of causes that enter through the Cybertipline system per year between the years 2014, 2015 and 2016, fix the difficulties to identify the perpetrators of the causes reported in the mentioned period of time and identify measures assigned or adopted in the Cases of child pornography reported through the Cybertipline system in which the perpetrator cannot be determined.